Analisis Kadar Vitamin C Bawang Putih dan Hitam dengan Metode Spektrofotometri UV-Vis: Analysis of Vitamin C Levels of Garlic and Black Garlic by UV-Vis Spectrophotometric Method - Magfira Jurwita; M. Nasir; Abdul Gani Haji (KOVALEN: Jurnal Riset Kimia, 2020)
An analysis of vitamin C levels of garlic and black garlic was done by UV-Vis spectrophotometric method. Garlic and black garlic contain a variety of nutrients and vitamins. Single and plural garlic is widely used as a medicine, besides garlic is currently also popular with garlic which is processed at temperatures between 60-80̊C with an environmental humidity of around 70-90% for 10-40 days. One of the vitamins contained in garlic includes vitamin C which acts as an antioxidant and is effective in dealing with free radicals. Vitamin C analysis was performed by the spectrophotometric method on the maximum wavelength is 250 nm with an absorbance value of 3.994. Results of analysis of vitamin C levels single garlic by 0.28% content of plural garlic by 0.27%. Vitamin C levels of single black garlic 0.29% (10 days), 0.31% (20 days), and 0.32% (30 days), plural black garlic Vitamin C levels 0.28% (10 days), 0.29% (20 days) and 0.31% (30 days).Based on ANOVA test results obtained there are differences in levels of vitamin C in single black garlic over several variations of time (days)and there are differences in levels of vitamin C in plural black garlic over several variations of time (days) because of Fcount ≥ Ftable.The coefficient of variation (KV) value is needed to test the level of accuracy of the analysis results. KV value in single garlic is 0.68% and plural garlic is 1.24%. KV value of single black garlic 0.3% (10 days), 0.25% (20 days), and 0.7% (30 days), KV of black garlic 0.55% (10 days), 0.61% (20 days), and 0.43% (30 days). Keywords: Single garlic, garlic plural, black garlic, fermentation, vitamin C levels